Tingkat Kepuasan Pengunjung Obyek Wisata Pantai Kuwaru Sanden Bantul Yogyakarta - Djoko Wijono (Jurnal Maksipreneur, 2014)
Research with the title: "The level of visitor satisfaction Kuwaru Beach Tourism Object Sanden, Bantul Yogyakarta", aims to investigate the characteristics of visitors or tourists, to determine the level of visitor satisfaction, when seen from the factors that influence, as well as to determine the most dominant influence on tourism visitor satisfaction levels.Factors thought to influence the satisfaction level of visitors is limited in the 8 factors: fees/entrance fee, the beauty of the beach, the cleanliness of the beach, playground, outdoor stage/venue, souvenir shop, SAR / health, location of parking. The survey results revealed that visitor characteristics by sex men 60% and women 40%; derived from DIY 69.3%, 30.7% outside DIY; seen from the age of visitors by 44% over the age of 50 years;Most visitors are high school education by 48%; and 29.3% of visitors to work as private sector workers. The level of visitor satisfaction is at a value of 3.98 which is located in criterion from 3.40 to 4.19 entering the satisfied category. The dominant factor influencing visitor satisfaction are: parking space factor with a value of 4.08 providing the highest level of satisfaction, followed by a factor of 4.03 and souvenirs to the value of SAR with a value of 4.00, whereas the rate factor is a factor kepuasanya lowest levies/entrance fee tourism with the value 3.84.